Skeletal Muscle Atrophy in Simulated Microgravity Might Be Triggered by Immune-Related microRNAs - Teodori, Laura; Costa, Alessandra; Campanella, Luigi; Albertini, Maria C. (Frontiers in Physiology, 2019)
Exposure to microgravity induces skeletal muscle disorders including atrophy, muscle force decrease, fibre-type shift. Microgravity also contributes to immune-function alterations and modifies microRNAs (miRs) expression. To understand the link between microgravity-induced skeletal muscle atrophy and immune function deregulation, a bioinformatics study was performed. The web platform MiRNet was used for miRs-targets interaction analysis from previous proteomic studies on human soleus (SOL) and vastus lateralis (VL) muscles. We predicted miRs targeting deregulated gene expression following bed rest as a model of microgravity exposure; namely, let-7a-5p, miR-125b-5p for over-expressed genes in SOL and VL; miR-1-3p, miR-125b-5p and miR-1-3p, miR-95-5p for down-expressed genes in VL and SOL. The predicted miRs have important immune functions, exhibiting a significant role on both inflammation and atrophy. Let-7a down-expression leads to proliferation pathways promotion and differentiation pathway inhibition, whereas miR-1-3p over-expression yields anti-proliferative effect, promoting early differentiation. Such conflicting signals could lead to impairment between proliferation and differentiation in skeletal muscles. Moreover, promotion of an M2-like macrophage phenotype (IL-13, IL-10) by let-7a down-regulation and simultaneous promotion of an M1-like macrophage (IL-6, TNF-α) phenotype through the over-expression of EEF2 lead to a deregulation between M1/M2 tuning, that is responsible for a first pro-inflammatory/proliferative phase followed by an anti-inflammatory pro-myogenic phase during skeletal muscle regeneration after injury. These observations are important to understand the mechanism by which inflammation may play a significant role in skeletal muscle dysfunction in spaceflights, providing new links between immune response and skeletal muscle deregulation, which may be useful to further investigate possible therapeutic intervention.